Partículas rugosas de sílica híbrida aplicadas na transesterificação catalítica - Zapelini, Iago William (Universidade Federal de São Carlos, 2019)
Heterogeneous catalysts are potentially responsible for reducing the cost of producing biodiesel, due to its reusability or use in continuous process. As-synthesized hybrid silicas, containing siloxy sites, can be used as catalysts for the transesterification and are interesting materials due to the facile control of their chemical and morphological properties. In this work, the effect of CTABr surfactant content and cosolvent alcohol chain length on the structural and catalytic properties of hybrid silicas containing occluded CTA+ cations was evaluated. All the prepared materials were actives in the model transesterification reaction. The surfactant concentration in the synthesis had a positive effect on the reaction activity, increasing the TOF¬0 by 2.5 times when the CTABr/TEOS molar ratio was increased from 0.1 to 0.8. This improvement in the catalytic activity can be attributed especially to the reduction of particle size and also to the formation of surface roughness in the silica particles. Likewise, when alcohols with a higher carbon chain was used, higher values of TOF0 were achieved, increasing by 1.8 times higher for the catalyst prepared with 1-butanol in comparison with the one prepared with ethanol. In addition, both variables had a positive effect on catalytic stability, showing that the use of higher surfactant concentration and alcohols with longer carbonic chains are efficient for improving the catalytic properties of hybrid silica particles.
Rough particles of hybrid silicas applied in catalytic transesterification
Keywords: Álcoois; Biodiesel; CTABr; Micelas; Silóxi; Surfactante; Alcohols; Micelles; Siloxy; Surfactant; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA